The Local Geoid Model of Cameroon: CGM05 - Kamguia, Joseph; Tabod, Charles T.; Nouayou, R.; Tadjou, J.M.; Manguelle-Dicoum, E.; Kande, H.L. (Nordic Journal of Surveying and Real Estate Research, 2007)
This paper deals with the geoid determination in Cameroon by a gravimetric solution. A number of data files were compiled for this work, containing about 62,000 points on land and ocean areas and also including data derived from satellite altimetry. A hybrid global geopotential model (EGM-GGM) supplied the longer wavelength components of this geoid model, CGM05. This global model is obtained by adjusting the GRACE model GGM02C to degree and order 360 using the harmonic coefficients of the model EGM96 beyond the maximal degree 200 of GGM02C. The medium wavelength components were computed using the best gridded residual gravity anomalies, by integration in Stokes’ formula. The digital terrain model GLOBE contributed to its short wavelength components. The residual terrain model (RTM) was applied to first determine a quasi-geoid model. This intermediate surface was converted to the geoid using a grid of simple Bouguer gravity anomalies. The validation of CGM05 is based on comparisons to global and regional geoids. A GPS/levelling geometric geoid computed in a small part of the target area shows that the absolute accuracy of this local geoid model is 14 cm. After a four-parameter fitting to the GPS/levelled reference surface, this absolute accuracy reduced to 11 cm.